Genotypic dynamics and dispersion in Colombian biomes of kdr mutations associated with resistance to pyrethroids in the Aedes aegypti mosquito (Diptera: Culicidae) - Aguirre-Obando, Oscar Alexander; Valencia-Marín, Bryan Steven; Duarte-Gandica, Irene (Revista de Biología Tropical, 2024)
Introduction: In Colombia, Aedes aegypti is present in 80 % of the country and little is known about the kdr mutations related to pyrethroids (PY) resistance, as well as the influence of different biomes (mainly temperature) and passive ground delivery transport on maintaining and disseminating populations with these mutations. Objective: To model the behavior of genotypic frequencies associated with the kdr Val1016Ile + Phe1534Cys mutation in A. aegypti populations, considering vector population movement between Colombian biomes through passive ground delivery transport. Method: We obtained data from the literature regarding population dynamics, mosquito life cycle parameters associated with temperatures for each Colombian biome, and ground cargo transportation, including truck transport. We also evaluated the impact of the evolutionary cost for the kdr Val1016Ile and Phe1534Cys mutations on oviposition and death rates. Results: Population behavior is influenced by the evolutionary cost of resistant genotypes and passive cargo transport. Once resistant genotypes arrive in a biome through truck-mediated mosquito transport, they persist. Conclusion: Passive migration through land cargo transport is essential for the dissemination of individual resistance carriers between different regions or biomes. Evolutionary cost plays a critical role in the dynamics of kdr mutations in A. aegypti populations.